A study of internal customer’s satisfaction toward materials services department of Petronas Penapisan (Melaka) Sdn. Bhd - Raja Samah, Raja Rusman (2000)
The recent internal problem on the usage of the new System, Applications, and Products version 3 module Maintenance and Materials Management (SAP R/3 - MMM) - pronounced S-Ay-Pca, not 'Sap'; has led researcher to take this opportunity to find out the actual causes of staff / end user's dissatisfaction. With internal customer (enduser) dissatisfaction and also problem encounter by warehouse personnel on updating data to the system becoming increasingly significant, researcher try to anaylse the level of dissatisfaction by end-user, warehouse personnel and weaknesses related to the root cause. Findings from this research suggests that the management need to re-look the reliablity of the internal control imposed in the system, accuracy of data entry and specification of materials which create problem to end-user as well as warehouse personnel. This research concludes with a discussion of the implications for marketing strategy formulation and implementation which includes the weaknesses of SAP system, materials delivery, inventory control, training and counter services. To enhance its image, Materials Services Department, particularly the Materials Operation Section must be willing to accept the significant weaknesses and engage drastic improvement on their services to increase its internal customers satisfaction.